CaZnOS:Nd3+ Emits Tissue-Penetrating near-Infrared Light upon Force Loading - Li, Lejing; Wondraczek, Lothar; Li, Lihua; Zhang, Yu; Zhu, Ye; Peng, Mingying; Mao, Chuanbin (ACS Applied Materials and Interfaces, 2018)
Mechanoluminescent (ML) materials are mechano-optical converters that can emit light under an external mechanical stimulus. All the existing ML materials can only emit light from near ultraviolet to red, which is outside the near-infrared (NIR) windows desired for biomechanical imaging. No studies have been done on doping rare earth (RE) ions with photoluminescence (PL) in the NIR region into a compound to form a ML material that emits NIR light in response to an external force. Here, we show that doping RE ions with a NIR PL into an inorganic compound does not usually result in the formation of a NIR ML material, which can only be achieved in the combination of Nd3+ ions and a CaZnOS compound among the combinations we studied. The newly discovered NIR ML material (CaZnOS:Nd3+) is biocompatible and can efficiently convert mechanical stress into NIR light over the first and second tissue-penetrating bioimaging window. Its NIR ML emission appeared at a very low force threshold (even when the material was shaken slightly), increased sensitively and linearly with the increase in the force (up to >5 kN), and could penetrate the tissue as deep as >22 mm to enable biomechanical detection. Such a force-responsive behavior is highly reproducible. Hence, CaZnOS:Nd3+ is a new potential ultrasensitive biomechanical probe and expands the ML application horizons into in vivo bioimaging.
CRIS-Team Scopus Importer:2023-04-20
Keywords: bioimaging; biomechanics; CaZnOS:Nd; mechanoluminescence; near infrared; tissue penetration